Study on Grain Refinement Mechanism of Internal Spline Tooth Profile by Vibration Assisted Cold Extrusion - Kai Zhang; Yong Wang; Ye Zhang; Yanyang Wang; Zufang Zhang; Ping Jin; Qingcheng Zhou (Jixie chuandong)
In order to study the microstructure evolution of the formed parts in the axial vibration cold extrusion process， the microstructure evolution process of the blank in the axial cold extrusion process is simulated by using the cellular automata method. It is found that the average grain size of internal spline processed by cold extrusion with auxiliary vibration is significantly smaller than that without auxiliary vibration. The effects of vibration frequency，vibration amplitude and extrusion speed on the microstructure of the formed parts are analyzed by orthogonal test. The results of variance analysis show that the vibration amplitude has the most significant influence on the average grain size at the tooth root，and the most significant influence on the grain size at the pitch circle and the top of the tooth is the vibration frequency and extrusion speed， the vibration frequency has the most significant influence on the average grain uniformity at the root and pitch circle of the formed part， and the extrusion speed has the most significant influence on the grain uniformity of the tooth top. The mechanism of the effect of auxiliary vibration parameters on grain refinement is summarized.